Implementasi Pendidikan Agama Islam yang Integratif (Antara Guru, Orang Tua, dan Masyarakat) - Medina Nur Asyifah Purnama (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2019)
National education aims to realize Indonesian people who are faithful and devoted. Achieving these objectives needs to be supported by the pattern of implementing an integrative education. The implementation of integrated or integrated education is the implementation of education that tries to combine several responsibilities of Islamic religious education that are not only the obligation of school teachers but also the obligations of parents and the community must also be responsible as in Article 54 of Law Number 20 Year 2003. For example, in the curriculum Elementary school, namely learning to read the Koran and prayer. Learning in school will never work, if parents don't give an example at home. Therefore, the teacher teaches and trains the parents of students who cannot read the Qur'an and prayers. Therefore, the formation of faith and piety which has been on the shoulders of religious teachers, now must be the duty of all. Thus, the education provided will be able to reach the goal because of the help of parents and guardians of students and the community.